ADMINISTRATIVE-LAW REGULATION SAFETY OF CIVIL AVIATION - Yeryashov, Yevgen (Proceedings of National Aviation University, 2017)
Purpose: the purpose of our research is an analysis the norms of the Air Code of Ukraine concerning aviation safety and academic literature with aim to give definition administrative-law regulation safety of civil aviation. Methods: using the methods of comparison and analysis in conjunction with formal legal determined by the nature are given definitions environmental safety, economic safety and information safety. Also is given definition administrative-law regulation safety of civil aviation. Results: in the context of analysis the norms of the Air Code of Ukraine and academic literature the author considers an aviation safety as a complex legal phenomenon that, on the one hand is a relatively stable condition, and on another consists of five elements. Аn environmental safety, economic safety and information safety should be given a definition and included in the Article 1 of the Air Code of Ukraine. The article provided the following definition of administrative-law regulation safety of civil aviation: it is carried out by the State overbearing influence on the operators of aircraft and other aviation activities by adopting regulations varying legal force (as well as authorization in to national legislation regional and international agreements) regarding a safe usage of aviation objectives in order to ensure of a safety of civil aviation. Discussion: in this article the author to consider of a concept of aviation safety and its elements. Also presents own definition of some elements of a safety of civil aviation and a concept of administrative-law regulation safety of civil aviation.